2021
DOI: 10.3390/antiox10010064
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in the Pathogenesis of Crohn’s Disease and the Interconnection with Immunological Response, Microbiota, External Environmental Factors, and Epigenetics

Abstract: Inflammatory bowel disease (IBD) is a complex multifactorial disorder in which external and environmental factors have a large influence on its onset and development, especially in genetically susceptible individuals. Crohn’s disease (CD), one of the two types of IBD, is characterized by transmural inflammation, which is most frequently located in the region of the terminal ileum. Oxidative stress, caused by an overabundance of reactive oxygen species, is present locally and systemically in patients with CD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 131 publications
0
52
0
1
Order By: Relevance
“…To preserve cellular homeostasis, the activity of prooxidants has to be compensated for by antioxidants. Antioxidant enzymes SOD, CAT, and GPX, are present in cells and have a primary role in detoxification [ 2 ]. Mrowicka et al found significantly lower SOD, CAT and GPX levels in IBD patients in relation to controls [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To preserve cellular homeostasis, the activity of prooxidants has to be compensated for by antioxidants. Antioxidant enzymes SOD, CAT, and GPX, are present in cells and have a primary role in detoxification [ 2 ]. Mrowicka et al found significantly lower SOD, CAT and GPX levels in IBD patients in relation to controls [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel diseases (IBDs), including Crohn’s disease (CD) and ulcerative colitis (UC), are chronic ailments of multifactorial etiology, affecting mostly the gastrointestinal (GI) tract [ 1 ]. IBD is a result of a complex interplay between genetic factors, changes in the colonic barrier function, immune system, intestinal microbiota, and environmental factors, such as diet, smoking, drugs, alcohol, or xenobiotics [ 1 , 2 ]. Constant exposure of the GI tract to risk factors leads to oxidative stress (OS): an overproduction of reactive oxygen species (ROS) and free radicals with accompanying insufficiency of endogenous antioxidant systems [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations